THE EFFECT OF TRAINING WITH SINGLE AND DOUBLE WEIGHT MACHINES AND EQUIPMENT ON THE MAXIMUM STRENGTH OF THE MUSCLES INVOLVED IN ACHIEVEMENT THE BENCH PRESS FOR ADVANCED POWERLIFTERS - Wissam Yasseen Burhan; Majid Abdul Hameed Rasheed (Journal Olahraga Rekat (Rekreasi Masyarakat), 2026)
Background. Maximal strength is influenced by several aspects including muscular coordination ability to produce force rapidly and adaptations to specific loads. Weight machines and resistance exercise equipment are popular training modalities among national and international elite-level teams. However, there is a paucity of evidence related to single and double weight machine exercise training in increasing maximal strength among advanced powerlifters. Objectives. The aim of the study was to determine and compare the effects of single weight machine and weight training using equipment on maximal muscle strength and bench press performance among advanced powerlifters. Method. The study used an experimental-equivalent groups design with pretest–posttest measures. Twenty-four advanced male powerlifters, aged 23–30 years, were recruited from Diwaniyah powerlifting team as participants. Sampling was done using stratified random sampling according to the competitors’ weight. Participants were assigned randomly to either the single-weight machine training group (n = 8), double-weight machine training group (n = 8), or control group (n = 8). The control group continued the coach’s regular training program throughout the study. Each intervention group trained three times per week for 8 weeks. Assessment of maximal muscle strength and bench press performance was conducted pre- and post-intervention. Results. Results revealed significant improvements in maximal strength and bench press performance in both experimental groups in comparison to the control group. There was a significantly greater increase in maximal strength performance using double weight machines than single weight machines. Conclusion. Resistance exercise programs using single and double weight machines enhanced maximal strength and bench press performance among advanced powerlifters. Findings provide evidence-based recommendations regarding strength training specificity among elite powerlifting competitors and support increased accuracy when programming by training modality.